2018
DOI: 10.1080/17470218.2016.1251472
|View full text |Cite
|
Sign up to set email alerts
|

Exceptionalist naturalism: Human agency and the causal order

Abstract: This paper addresses a fundamental question in folk metaphysics: How do we ordinarily view human agency? According to the transcendence account, we view human agency as standing outside of the causal order and imbued with exceptional powers. According to a naturalistic account, we view human agency as subject to the same physical laws as other objects and completely open to scientific investigation. According to exceptionalist naturalism, the truth lies somewhere in between: We view human agency as fitting bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…3, participants' intuitions about Chance-arguably our strongest measure of intrusion (see below for details)-were much weaker in the robot cases than in the agent cases. 21 This comports with the findings by Turri (2017c) whereby people tend to view the behavior of robots as less avoidable (i.e., more deterministic) and view the behavior as agents as more avoidable (i.e., more indeterministic). According to his findings, people tend to believe that whereas humans have the ability do otherwise (which is an important element of free will), robots largely lack this ability.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…3, participants' intuitions about Chance-arguably our strongest measure of intrusion (see below for details)-were much weaker in the robot cases than in the agent cases. 21 This comports with the findings by Turri (2017c) whereby people tend to view the behavior of robots as less avoidable (i.e., more deterministic) and view the behavior as agents as more avoidable (i.e., more indeterministic). According to his findings, people tend to believe that whereas humans have the ability do otherwise (which is an important element of free will), robots largely lack this ability.…”
Section: Discussionsupporting
confidence: 66%
“…For on the conditional reading, this amounts to nothing more than the fact that had the past or the laws been different, the robot could have and would have done something different. Given that Turri (2017c) found that people don't think robots have the ability do otherwise precisely because they are taken to be more deterministic, this suggests that the notion of ability people are applying in these sorts of cases is the unconditional ability.…”
Section: % 52%mentioning
confidence: 99%
“…We propose one explanation for the discrepant findings regarding folk compatibilism: People are motivated to uphold their beliefs in free will and moral responsibility. Most laypersons believe in free will (e.g., Sarkissian et al, 2010) and disbelieve determinism (Nichols, 2004; Nichols and Knobe, 2007; Turri, 2017b), and people tend to evaluate information in a biased manner that favors their desired beliefs (e.g., Lord et al, 1979; Kunda, 1990). Thus, people are likely to report that free will is possible regardless of experimentally imposed constraints (Feltz and Millan, 2013), particularly when desiring to uphold moral responsibility (Clark et al, 2014, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Incompatibilists, on the other hand, argue that compatibilist intuitions may result from people importing indeterminacy into deterministic scenarios. Recent work has revealed that most people are natural indeterminists about human agency (Knobe, 2014;Monroe, Dillon, & Malle 2014;Turri, 2017). It is therefore unsurprising that indeterminism seems to influence people's intuitions about free will in response to deterministic scenarios.…”
Section: Folk Intuitions and The Comprehension Problemmentioning
confidence: 99%